Emerging third generation private label brands: retailers' and consumers' perspectives towards leading Indian retail chains. (5th June 2020) - Singh, Ajay; Singhal, Rakesh Kumar
This study is an attempt to explore retailer's motivation to acquire private label brands in their stores and realise the same through exploring consumer preferences, behaviour and attitude. To conduct the study, responses were collected from food and grocery consumers of Indian leading retail chain, Big Bazaar. Data Collection was done through structured questionnaire from 325 households who have visited Big Bazaar Store and Linear Regression Analysis was performed. Findings of the study revealed a positive correlation between the perceived quality and price consumers willing to pay towards private label products. It also found strong correlation between value perceptions of private label brands with overall stores image also store loyalty is positively associated with value perception of private label brands. This study gives an insight to Indian retailers about the consumer preferences towards buying private label brands.